(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
In article the original key for determination and the cheklist of family Limoniaceae Lincz. Ukrainian flora`s is resulted. In the cheklist for each species the nomenclature citation, basionim, basic synonym`s, the specified data concerning distribution to Ukraine and the general are presented. The taxonomical position of the author proves in notes on everyone taxon, the most reliable diagnostic feature are specified. Original nomenclature changes are offered some. In particular, new combinations in a rank of subspecies for 3 species from complex Limonium tomentellum aggr. - L. tomentellum (Boiss.) O.Kuntze subsp. alutaceum (Steven) Moysiyenko comb. nova, L. tomentellum (Boiss.) O.Kuntze subsp. donetzicum (Klokov) Moysiyenko comb. nova., L. tomentellum (Boiss.) are offered O.Kuntze subsp. hypanicum (Klokov) Moysiyenko comb. nova; concerning last subspecies also it is proved illegitimacy of its consideration at an intraspecific level in structure of L. gmelinii (Willd.) O.Kuntze, (L. gmelinii (Willd.) O.Kuntze var. hypanicum (Klokov) Paw. That L. gmelinii subsp. hypanicum (Klokov) Sόo). It is proved, that Limonium caspium (Willd.) Gams and L. danubiale Klokov should rate in structure of Limonium bellidifolium (Gouan) Dumort. In a final variant family Limoniaceae Lincz. in flora of Ukraine it is presented by 3 genus, 16 species and 3 subspecies: Armeria (DC.) Willd. (A. maritima (Mill.) Willd., A. pocutica Pawł., A. vulgaris Willd.), Goniolimon Boiss. (G. besserianum (Schult.) Kusn., G. graminifolium (Ait.) Boiss., G. rubellum (S.G.Gmel.) Klokov, G. tataricum (L.) Boiss.), Limonium Mill. (L. bellidifolium (Gouan) Dumort., L. bungei (Claus) Gamajun., L. gmelinii (Willd.) O.Kuntze, L. platyphyllum Linch., L. sareptanum (A.Beck.) Gams, L. sinuatum (L.) Mill., L. suffruticosum (L.) O.Kuntze, L. tomentellum (Boiss.) O.Kuntze subsp. alutaceum (Steven) Moysiyenko, L. tomentellum (Boiss.) O.Kuntze subsp. donetzicum (Klokov) Moysiyenko, L. tomentellum (Boiss.) O.Kuntze subsp. hypanicum (Klokov) Moysiyenko, Limonium tsсhurjukiense (Klokov) Lavrenko ex Klokov), including Armeria maritima and Limonium sinuatum cultivated.